Analisis Buku Teks Bahasa Indonesia Kelas IV Sekolah Dasar - Muchtar Muchtar (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2002)
Textbook is a dominant factor affecting learning outcomes. This research aimed to examine the relevance of the textbook of Bahasa Indonesia to the Elementary School Curriculum 1994 in terms of its approaches, objectives of the course, learning themes, and learning contents. In this descriptive study, the researcher's role was as a subject and as the main instrument. Through a documentary analysis, this research concluded that, in terms of its approaches, objectives, learning themes, and learning contents, the textbook of Bahasa Indonesia was relevant to the curriculum. Nevertheless, there were a number of learning items that were not accomodated in the textbook.